Construction and application of a CRISPR/Cas9-assisted genomic editing system for Corynebacterium glutamicum - Chengzhen Yao; Xiaoqing Hu; Xiaoyuan Wang (AMB Express, 2021)
Abstract Corynebacterium glutamicum is widely used as microbial cell factory for various bioproducts, but its genomic editing efficiency needs to be improved. In this study, a highly efficient CRISPR/Cas9-assisted genomic editing system for C. glutamicum was constructed. This system mainly involves a plasmid and can be used for both gene insertion and deletion in the chromosome of C. glutamicum. The recombinant plasmid for the target gene containing all the editing elements, and first constructed it in E. coli, then purified and transformed it into C. glutamicum. This temperature-sensitive plasmid was cured at high temperature after the genomic editing was completed in C. glutamicum. Using this genetic editing system, the genetic editing efficiency in C. glutamicum ATCC 13032 could reach 95%. The whole work of editing could be done in 8–9 days and showed most time-saving compared to the reported. Using this system, the native promoter of gdhA1 in ATCC 13032 has been replaced with the strong promoter PtacM, and more than 10 genes in ATCC 13032 have been deleted. The results demonstrate that this CRISPR/Cas9-assisted system is highly efficient and very suitable for genome editing in C. glutamicum.